2009
DOI: 10.1099/jmm.0.009993-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug-resistant Helicobacter pylori in Bulgaria

Abstract: The aim of this study was to evaluate the presence and prevalence of multidrug antibacterial resistance in Helicobacter pylori in Bulgaria from 2005 to 2008. The resistance in 828 untreated adults, 124 treated adults and 105 untreated children was, respectively, 26.5, 50.8 and 16.2 % for metronidazole; 18.4, 45.2 and 19 % for clarithromycin; 1, 2.4 and 0 % for amoxicillin; 4.4, 10.6 and 1.9 % for tetracycline; and 9, 14.5 and 5.8 % for ciprofloxacin. Triple resistance to the evaluated agents was uncommon and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 32 publications
4
25
2
2
Order By: Relevance
“…Five H. pylori strains were resistant to AMX, MNZ and CLR, two of them exhibiting quadruple resistance. Resistance to four of the five antibacterials tested was found in 0.7% of the untreated and 1.8% of the treated adults [26]. Quadruple resistance of H. pylori has not been reported in Europe and the USA in last 5 years, although a study from India reported this type of resistance in 2.6% of isolates [27].…”
Section: Discussionmentioning
confidence: 93%
“…Five H. pylori strains were resistant to AMX, MNZ and CLR, two of them exhibiting quadruple resistance. Resistance to four of the five antibacterials tested was found in 0.7% of the untreated and 1.8% of the treated adults [26]. Quadruple resistance of H. pylori has not been reported in Europe and the USA in last 5 years, although a study from India reported this type of resistance in 2.6% of isolates [27].…”
Section: Discussionmentioning
confidence: 93%
“…In a region with high rates of clarithromycin resistance, sequential or concomitant therapy is recommended as the first-line H. pylori eradication treatment [25] . The primary reason for the growth in antibiotic resistance is the emergence of point mutations in the H. pylori genome [26] . Thus, the development of novel treatment methods to increase eradication rates and reduce antibiotic resistance is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In areas with high rates of clarithromycin resistance, the first option is a sequential or concomitant regimen [6] . The main reason for the increase in antibiotic resistance is the accumulation of point mutations in the H. pylori DNA, which are in most cases associated with the overuse of antibiotics [7] . Therefore, the development of a new treatment regimen that not only improves the eradication rate but also reduces the frequency of adverse effects remains the principal challenge.…”
Section: Introductionmentioning
confidence: 99%